2015
DOI: 10.1111/cen.12862
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty pancreas disease and Nonalcoholic fatty liver disease: more than ectopic fat

Abstract: SummaryObjective The aim of this study was to evaluate the metabolic effects of fatty pancreas (nonalcoholic fatty pancreas disease -NAFPD) in a group of obese paediatric patients with nonalcoholic fatty liver disease (NAFLD). Methods We included 121 consecutive children with echographic evidence of hepatic steatosis. All patients underwent to abdominal ultrasound to evaluate pancreatic echogenic pattern. We divided the patients into two groups on the basis of the presence of fatty pancreas. In all patients li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 31 publications
2
94
4
4
Order By: Relevance
“…Recent epidemiological studies reported a 16% prevalence of NAFPD in the general adult population, with an increase of this percentage in obese patients with NAFLD, while the prevalence in the paediatric population is still not available 4. Uygun et al 24 noted that under US examination, the prevalence of fatty pancreas was approximately 50% in adults with biopsy proven NAFLD, illustrating the close association these two conditions have to one another.…”
Section: Nafpd and Nafldmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent epidemiological studies reported a 16% prevalence of NAFPD in the general adult population, with an increase of this percentage in obese patients with NAFLD, while the prevalence in the paediatric population is still not available 4. Uygun et al 24 noted that under US examination, the prevalence of fatty pancreas was approximately 50% in adults with biopsy proven NAFLD, illustrating the close association these two conditions have to one another.…”
Section: Nafpd and Nafldmentioning
confidence: 99%
“…Contrary to those of NAFLD, the potential consequences of pancreatic fat accumulation are as of yet, not well established 4. Ongoing fatty infiltration and endocrine/exocrine dysfunction of the pancreas is mediated by the direct toxic effect of fat on pancreatic acinar cells and islets 5.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations